As encenações da Batalha do Pulador : memórias e representações - Silva, Ernani da (2013)
A Pulador Battle performance has been doing, in Passo Fundo/RS region, since 1988. All over that time it wasn t played just for some years. The playing has come back some years ago by traditional region groups engage to reproduce it year after year. Nowadays the event is been in its 6th edition. The battle grown up inside to a historical context from the Brazilian Federalist Revolution in 1893, when a transition moment which the monarchy government was been change to republic. That historical fact happened on June 27, 1894, in Pulador district, around Passo Fundo Region, was recognized in the Planalto Médio Rio-Grandense as a violent and fratricide event. After 118 years, the performing has been assumed many characterizations. Many of them is a spectacular, theatrical and media performance which pays attention to a public show, on Brasil Avenue and also in Pulador field, has been dramatized a march s Republic and Maragata troops. In that way, the work, based on a research in historical facts data, intends to understand the performing features, showing some successful rooting aspects about historical memory as a social identification, myth, imaginary, playing and acting, represented through many performances since 1998 to 2012, when, in the last time, there was the 6th edition. This dissertation intends to present a criterion research and others many goals about the Pulador Battle history and its influence in region social groups.